2013
DOI: 10.1111/1467-9248.12041
|View full text |Cite
|
Sign up to set email alerts
|

Haves and Have-Nots before the Law Lords

Abstract: One important characteristic of justice, and thus of our judicial system, is impartiality. One type of judicial impartiality is impartiality between litigants who command status and material resources ('haves') and those who do not ('have-nots'). I investigate the success of 'haves' in appeals to the House of Lords between 1969 and 2003. I investigate two separate paths by which 'haves' might succeed more: relative status advantage over other litigants, and being able to hire more experienced and more successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Governments have slightly better odds of success than the baseline category (limited companies), as we might expect given the literature on government advantage in litigation (McGuire, 1998;McCormick, 1993;Hanretty, 2013;cf. Smyth, 2000).…”
Section: Q(a X; A) = αmentioning
confidence: 67%
See 2 more Smart Citations
“…Governments have slightly better odds of success than the baseline category (limited companies), as we might expect given the literature on government advantage in litigation (McGuire, 1998;McCormick, 1993;Hanretty, 2013;cf. Smyth, 2000).…”
Section: Q(a X; A) = αmentioning
confidence: 67%
“…The literature in political science has concentrated on appellate outcomes, which can in most cases be reduced to a binary variable (either the appeal succeeds or it does not), and which has employed indirect measures of lawyer quality (for example: Justice Blackmun's letter grades assigned to counsel at oral argument (Johnson et al, 2006) or experience (Haynie and Sill, 2007) or senior counsel status (Szmer et al, 2007) or past record (Hanretty, 2013)) to test whether better counsel win more appeals. A more general literature in empirical legal studies has focused on continuous outcomes, sometimes monetary outcomes in personal injury cases (Moorhead et al, 1994;Rosenthal, 1974) but more often sentence lengths in criminal trials, where the stakes are particularly high for clients (Abrams and Yoon, 2007;Shinall, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…High win rates for the state have been reported for decades in various empirical studies, in Israel and in other countries (Dotan 1999a; Cohen & Spitzer ; Wheeler et al. :418; Songer & Sheehan :241; Huang ; Hanretty ; Weatherall & Jensen ; McCormick ; Atkins :894–95; He & Su ). For example, in the United States, the IRS National Taxpayer Advocate's annual report to Congress for 2011 indicated that the IRS's win rate is over 90 percent in its key court proceedings.…”
Section: Hypothesis I: the Effect Of Law Reforms On Win Ratesmentioning
confidence: 99%
“…Any dividing line by Chris Hanretty, which found that the relative experience of counsel had an effect on the decisions of the House of Lords. 230 If true, this may also be a factor in the 'inequality of arms' problem, in that some corporate claimants have better access to experienced counsel than individual defendants. Another interpretation might be that unrepresented defendants are less likely to be advised to settle their cases.…”
Section: Alternative Legal Remediesmentioning
confidence: 99%